Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1111/chd.12195
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Profiles of Perioperative Serum C-Reactive Protein Levels in Neonates Undergoing the Norwood Procedure or Arterial Switch Operation

Abstract: Neonates undergoing NP have a higher level of serum CRP, reflecting a greater systemic inflammatory response before and after CPB than those undergoing ASO, despite of shorter CPB and ACC. The higher level of serum CRP was associated with a significantly higher level of arterial lactate in the NP group than in the ASO group. This may suggest an important role of systemic oxygen transport in systemic inflammatory response in addition to CPB in neonates with congenital heart defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…A total of 21 studies were included in the pooled analyses. 5,[15][16][17][18][19][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] Data were collected for the following timepoints: pre-CPB, end of CPB, 1 h after CPB, POD 1, POD 2, POD 3, POD 4, and POD 5. Figure 1 outlines the study search strategy while Table 1 provides an overview of included studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 21 studies were included in the pooled analyses. 5,[15][16][17][18][19][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] Data were collected for the following timepoints: pre-CPB, end of CPB, 1 h after CPB, POD 1, POD 2, POD 3, POD 4, and POD 5. Figure 1 outlines the study search strategy while Table 1 provides an overview of included studies.…”
Section: Resultsmentioning
confidence: 99%
“…A systemic inflammatory response is a known cause of cardiovascular and pulmonary dysfunction 21,23 . It can be multifactorial in origin and may be triggered during CHS with CPB due to blood contact with foreign surfaces, presence of endotoxemia and development of ischemia and reperfusion injury 24,34,36 . However, the leading cause of systemic inflammatory response after CPB is the interaction of blood components with artificial surfaces of the extracorporeal circuit 24 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The paediatric literature on the kinetics of PCT and CRP in the post-operative period is primarily focused on the postneonatal age group or patients undergoing cardiac surgery. [3][4][5][6][7][8][9][10][11] There are scarce data on PCT or CRP among neonates undergoing non-cardiac surgery. Celik et al showed that CRP concentrations on post-operative days (PODs) 2, 4 and 6 were significantly higher than baseline after neonatal abdominal surgery.…”
Section: What This Paper Addsmentioning
confidence: 99%
“…9 However, serial levels (which provide the ''CRP velocity'') may differentiate postoperative infection, 10 and CRP may become elevated in certain subpopulations such as postoperative Norwood patient. 11 Interestingly, one study of patients after the Norwood procedure found a correlation between elevated serial CRP measurements and impaired neurocognitive development at age two. 12 Similarly, CD64 has been evaluated as a biomarker of infection.…”
Section: Fever In the Pediatric Cicumentioning
confidence: 99%